Foot orthoses for the prevention of lower limb overuse injuries in naval recruits: study protocol for a randomised controlled trial - Daniel R. Bonanno; George S. Murley; Shannon E. Munteanu; Karl B. Landorf; Hylton B. Menz (Journal of Foot and Ankle Research, 2015)
Abstract Background Foot orthoses are frequently used for the prevention of lower limb overuse injuries but evidence for their effectiveness is limited. The primary aim of this study is to determine if prefabricated foot orthoses reduce the incidence of lower limb overuse injuries in naval recruits undertaking 11 weeks of basic training. Methods This study is a participant and assessor blinded, parallel‐group, randomised controlled trial. The trial will recruit participants undertaking 11 weeks of basic training at the Royal Australian Navy Recruit School, Cerberus, Victoria, Australia. Participants will be randomised to a control group (flat insole) or an intervention group (prefabricated foot orthosis). Over the 11 weeks of basic training, participants will document the presence and location of pain in weekly self‐report diaries. The end‐point for each participant will be the completion of 11 weeks of basic training. The primary outcome measure will be the combined incidence of four lower limb injuries (medial tibial stress syndrome, patellofemoral pain, Achilles tendinopathy, and plantar fasciitis/plantar heel pain) which are common among defence members. Secondary outcome measures include: (i) overall incidence of lower limb pain, (ii) severity of lower limb pain, (iii) time to injury, (iv) time to drop‐out due to injury, (v) adverse events, (vi) number of lost training days, (vii) shoe comfort, and (viii) general health status. Data will be analysed using the intention‐to‐treat principle. Discussion This randomised controlled trial will evaluate the effectiveness of prefabricated foot orthoses for the prevention of common lower limb overuse injuries in naval recruits. Trial registration Australian New Zealand Clinical Trials Registry: ACTRN12615000024549.